The Relationship Between Creatinine Levels and Hemoglobin Levels in Patients with Type 2 Diabetes Mellitus - Betti Rosita Betti; Marisa Marisa; Aisyi Annur (World Health Digital Journal, 2025)
Type 2 diabetes mellitus is a chronic metabolic disease often associated with microvascular complications, such as diabetic nephropathy, which can affect blood creatinine and hemoglobin levels. Elevated creatinine levels and decreased hemoglobin levels (anemia) are common complications that worsen patients’ conditions. This study aims to determine the relationship between creatinine and hemoglobin levels in patients with type 2 diabetes mellitus at the Pasaman Barat Regional General Hospital. This is a descriptive-analytical study using a cross-sectional approach. The sample consisted of 100 inpatients and outpatients who met the inclusion criteria. Data were obtained through laboratory tests measuring creatinine levels using a SanyMed Instrument spectrophotometer and hemoglobin levels using a Sysmex hematology analyzer. The results of the chi-square test showed a significant association between creatinine levels and hemoglobin levels (p = 0.000). The conclusion of this study is that there is a significant association between creatinine levels and hemoglobin levels in patients with type 2 diabetes mellitus. Monitoring these two parameters is important for detecting early complications and improving patients’ quality of life.